Analyses of Non-bonding Length, Partial Atomics Charge and Electrostatic Energy from Molecular Dynamics Simulation of Phospholipase A2 – Substrate - Nirwan Syarif; Dedi Rohendi (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2016)
Abstract: This paper reports molecular dynamics simulation of phospholipase A2 (PLA2)– substrate that has been done. Non-bonding length, partial atomic charge and electrostatic energy were used to evaluation the interaction between PLA2 and substrate. The research was subjected for three types of PLA2 of different sources, i.e, homo sapien, bovinus and porcinus, by using computer files of their molecular structures. The files with code 3elo, 1bp2, dan 1y6o were downloaded from protein data bank. Substrate structure can be found in 1y60 and was separated from its enzyme structure and docked into two other PLA2 structures for simulation purpose. Molecular dynamics simulations were done for 30000 steps with constant in number of molecules, volume and temperature (NVT). The results showed the existing of flip-flop mechanism as basic feature of PLA2 – substrate reactions. Interaction length analysis results indicated the presence of water molecules on the structures of 1bp2 and 3elo at the time of the simulation was completed. The existence of aspagine at the reaction site confirmed the theory that this amino acid is responsible for the survival of the reaction. the electrostatic energy increased substantially in the interaction after homo sapien PLA2 (3elo) and Bovinus (1bp2) with the substrate. Inverse effect took place in the PLA porcinus (1y6o).Keywords: flip flop, inflammation, in-silico, simulation Abstrak (Indonesian): Telah dilakukan penelitian tentang simulasi dinamika molekuler pada Situs Reaksi Phospholipase A2 (PLA2) dengan substratnya. Analisis panjang non-ikatan, muatan atom parsial dan energi elektrostatis digunakan untuk menilai interaksi antara PLA2 dan substratnya. Penelitian dilakukan pada tiga jenis sumber PLA2, yaitu homo sapien, bovinus dan porcinus dengan menggunakan file komputer untuk struktur molekul dengan kode 3elo, 1bp2, dan 1y6o. Pada file 1y60 terdapat struktur substrat yang dapat ditemukan secara alamiah. Kedua file lainnya tidak mengandung struktur molekul substrat. Simulasi dinamika molekul dilakukan untuk 30.000 langkah dengan konstan dalam jumlah molekul, volume dan suhu (NVT). Hasil penelitian menunjukkan keberadaan mekanisme flip-flop sebagai fitur dasar reaksi PLA2 - substrat. Hasil analisis panjang interaksi menunjukkan bahwa kehadiran molekul air pada struktur 1bp2 dan 3elo pada saat simulasi dilakukan. Keberadaan aspagine di lokasi reaksi menegaskan teori bahwa asam amino ini bertanggung jawab untuk kelangsungan hidup reaksi. energi elektrostatik meningkat secara substansial dalam interaksi setelah homo sapien PLA2 (3elo) dan Bovinus (1bp2) dengan substrat. efek terbalik terjadi di porcinus PLA (1y6o).Kata kunci: flip flop, inflamasi, peradangan, in-silico, simulasi